2006
DOI: 10.1128/aac.00578-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metacestodicidal Activities of Genistein and Other Isoflavones against Echinococcus multilocularis and Echinococcus granulosus

Abstract: Echinococcus multilocularis and Echinococcus granulosus metacestode infections in humans cause alveolar echinococcosis and cystic echinococcosis, respectively, in which metacestode development in visceral organs often results in particular organ failure. Further, cystic hydatidosis in farm animals causes severe economic losses. Although benzimidazole derivatives such as mebendazole and albendazole are being used as therapeutic agents, there is often no complete recovery after treatment. Hence, in searching for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 42 publications
3
58
0
1
Order By: Relevance
“…Besides other targets, genistein acts on a number of signalling pathways by functioning as a kinase inhibitor (tyrosine kinase, MAP kinase, ribosomal S6 kinase). Recent studies have shown that genistein is highly effective against E. multilocularis metacestodes in vitro (Naguleswaran et al 2006). However, genistein has a disadvantage, in that it also exerts oestrogenic effects by binding to oestrogen receptor-b, which renders genistein unfavourable for long-term treatment.…”
Section: (I) Chemotherapeutical Activities Of Anti-infective Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides other targets, genistein acts on a number of signalling pathways by functioning as a kinase inhibitor (tyrosine kinase, MAP kinase, ribosomal S6 kinase). Recent studies have shown that genistein is highly effective against E. multilocularis metacestodes in vitro (Naguleswaran et al 2006). However, genistein has a disadvantage, in that it also exerts oestrogenic effects by binding to oestrogen receptor-b, which renders genistein unfavourable for long-term treatment.…”
Section: (I) Chemotherapeutical Activities Of Anti-infective Drugsmentioning
confidence: 99%
“…Therefore, a number of isoflavonoids that do not carry this hydroxylgroup have been tested in vitro and do not meet the steric requirements to bind to the oestrogen receptor-beta. One of these compounds, Rm6423, exhibits a pronounced anti-parasitic activity against E. multilocularis metacestodes as well as against E. granulosus metacestodes and protoscoleces (Naguleswaran et al 2006). Moreover, an examination of culture medium revealed increased leakage of parasite proteins into the medium during treatment, and zymography demonstrated a loss of the activity of metalloproteases.…”
Section: (I) Chemotherapeutical Activities Of Anti-infective Drugsmentioning
confidence: 99%
“…We have therefore tested a number of isoflavonoids in vitro, which do not carry this hydroxylgroup and therefore do not meet the steric requirements to bind to the oestrogen receptor-b. One of these compounds, Rm6423, exhibits pronounced antiparasitic activity against E. multilocularis metacestodes, as well as against E. granulosus metacestodes and protoscoleces (Naguleswaran et al, 2006). Further, examination of culture medium revealed increased leakage of parasite proteins into the medium during treatment, and zymography demonstrated a loss in the activity of metalloproteases.…”
Section: (2) Studies On Antiproliferative Drugsmentioning
confidence: 99%
“…However, no ideal (both effective and safe) scolicidal agent has been deviced yet. The unacceptable sideeffects of the scolicidal agents cause limitation to their use (Naguleswaran et al, 2006). Surgery (radical or conservative) is usually complemented by pre and/or post-surgical chemotherapy.…”
Section: Cystic Echinococcosis (Ce) Is a Chronic Zoonosis Caused By Tmentioning
confidence: 99%